Determinant of Operational Cost Budget Fluctuations at Balai Kekarantinaan Kesehatan Kelas I Kupang - Anyelayenita Padu; Maria (Journal of Business, Accounting and Information Technology, 2026)
Fluctuations in operational cost budgets pose significant challenges to public sector financial management, particularly in health institutions that require funding stability to ensure service sustainability. This study aims to analyze the factors influencing operational budget fluctuations at Balai Kekarantinaan Kesehatan Kelas I Kupang and to examine the strategies implemented to manage these dynamics. Using a descriptive qualitative approach with a case study design, data were collected through in-depth interviews, observations, and document analysis of budget planning and realization reports for the 2022–2024 period. The findings reveal that external factors such as changes in central government policies, shifting national priorities, and budget allocation adjustments from ministries to regional technical units, are the primary drivers of budget fluctuations. Internal factors include limited planning capacity, suboptimal coordination among program managers, inadequate budget monitoring mechanisms, and the absence of operational reserve funds. To address these challenges, the institution applies strategies such as budget revisions, activity reprioritization, and cross-unit coordination. This study contributes to the literature on public sector budgeting by highlighting the interaction between external policy dynamics and internal managerial capacity, emphasizing the importance of strengthening planning and budget control systems to enhance financial stability in health quarantine institutions.